Integrasi Pembelajaran Kanji dengan Pembelajaran Sakubun untuk Meningkatkan Kemampuan Menulis - Astami, Timur Sri; Ningrum, Rosita; Budihardja, Felicia (Lingua Cultura, 2014)
Research aims to find the influence of strategies used in intermediate kanji learning, i.e. in a more applicative class using kanji, on middle kanji and composition class (sakubun). Research viewed and compared the influence of students’ mark in Intermediate Kanji with their mark in Sakubun. The questionnaire used in this research was the Strategy Inventory for Language Learning (SILL) consisting of 50 questions associated with types of strategy to learn kanji. The result obtained using T-test and correlation test was the students’ mark in kanji affected their mark in Sakubun. The relationship is the higher mark in kanji, the higher mark in Sakubun. As a conclusion, student essay writing ability is affected by the numbers of kanji remembered and used by students.